Determination of the lowest unit price through the value-added approach for Arabica Coffee Commodities in North Toraja Regency. Issue 1 (March 2020) - Rico,; Darma, R; Asrul, L
Abstract: Smallholder plantations in South Sulawesi province produce an average of 12.50% of Indonesia's Arabica coffee, equivalent to 20.10 thousand tons per year. In 2015 Arabica coffee produced by community plantations in the province reached 20.35 thousand. One of the largest Arabica coffee production centers in South Sulawesi province is in North Toraja Regency, in 2017 it gave a production share of 10.37% or a total production of 2.11 thousand tons. However, the current problem in North Toraja Regency is the low purchase value of collectors who come directly to farmers' gardens and appreciate the Arabica coffee of Rp. 18, 000 / liter which still has epidermis, if converted to kilograms requires around 2.1 liters, which if the total is only Rp. 36, 000 / kg. This study aims to formulate the lowest unit price policy for Arabica coffee in the North Toraja regency which is used as a reference for the average selling price of Arabica coffee (actual price). This research was conducted in North Toraja Regency, South Sulawesi province using purposive informants, which were analyzed descriptively quantitatively. The results showed that the lowest unit price of the coffee commodity can be formulated in the amount of Rp. 28, 000 / liter by increasing the price received by farmers by Rp. 10, 000, by considering prices at the level of traders and companies so that they continue to provide benefits for each marketing institution. This policy will have an impact on increasing the productivity and welfare of coffee farmers so that the sustainability of coffee commodity farming in Indonesia is increasing.